Susceptibility of European pear genotypes in a gene bank to pear psylla damage and possible exploitation of resistant varieties in organic farming - Benedek, P.; Szabó, T.; Soltész, M.; Szabó, Z.; Konrád-Németh, C. (International Journal of Horticultural Science, 2010)
We evaluated 285 pear genotypes (commercial cultivars, ancient local varieties, unnamed local strains, seedlings, wild seedlings) in the largest gene bank of pear in Hungary from the point of view of psylla resistance to explore their possible exploitation in organic farming. We have found some 10 new resistant types (Bókoló körte, Bôtermô Kálmán, Füge alakú körte, Nagyasszony körte, Nyári Kálmán, Rozs nyári körte, Viki körte, Pb-242, Pb-299, 0-632) and 7 highly tolerant ones (Cure-6, Kései Kálmán, Kieffer, Kieffer Éd, Steiner, Téli Kálmán, II. B-3- 6/4, 96-16/5) (Table 1). These made up 3.5 + 2.8 per cent of the investigated genotypes, while 93.7 per cent of them were susceptible to pear psylla damage. Taking earlier and present results into account we can list more than 30 European pear cultivars being resistant or highly tolerant to pear psylla infestation and damage. In fact, the list of resistant and highly tolerant cultivars may serve as a basis selecting pear cultivars fitting to the specific requirements of the organic farming. By the end we can conclude that there is some real hope to exploit some resistant or highly tolerant ancient or local cultivars in organic farming but further investigations are needed to estimate their yield capacity and fruit quality.